Longitudinal changes in the use of prepositions among Malaysian undergraduates / Elfreda Floria L. Danny - Elfreda Floria, L. Danny (2017)
The concept of multilingualism in second language acquisition (SLA) studies has recently raised the interest of many researchers in the field of SLA. In that, the argument that a need for a change of perspective in the study of SLA is raised. At the same time, the need for longitudinal learner data that could be used for SLA study was made known (Ortega & Brynes, 2008). In response to these, the study reported in this dissertation aims to investigate language development by building a corpus of learner language collected over time. Using the Antconc 3.4.4w (Windows) 2014, the study focused on the use of two prepositions of and to in order to analyse language as used by multilinguals. It was found that language development takes place in a non-linear and complex manner (Larsen-Freeman, 2006). At the same time, language users are found to be more focused on meaning making rather than the structure of the language used (Chau, 2015; Larsen-Freeman, 2015). The need for language teachers to acknowledge the bi/multilingual practice in addition to the complexity of language learners in the language classroom should then be highlighted. This may then effect change in the classroom practice as well as the English language education in Malaysia.